Studi Lanskap Linguistik: Bilingualisme dan Multilingualisme pada Papan Penamaan Bisnis Kuliner Jepang di Kota Malang Jawa Timur - Nadia Irma Della Devina; Ismatul Khasanah; Eni Sugiharyanti (IZUMI, 2024)
This research focuses on the phenomena of bilingualism and multilingualism that reflected in the name boards for Japanese culinary businesses in Malang City especially in Lowokwaru District as the data sources of this study. In line with these data sources, the linguistic landscape theory of Laundry & Bourhis (1997) is used to analyze the phenomena that occur. The research method used is a descriptive qualitative method. The results of this study found 9 data in the form of Japanese culinary business naming boards in Lowokwaru sub-district consisting of 6 bilingual data (Japanese-English), 2 bilingual data (Japanese-Indonesian) and 1 multilingual data consisting of (Japanese-English-Javanese). The use of foreign languages on culinary business signboards is a reflection of the reality of symbolic functions and informative functions related to the mindset of people who feel that the use of foreign languages is a form of modernity, has a selling point and more attractive. Keywords: Linguistic Landscape, Japanese Culinary Businesses, Bilingualism, Multilingualism gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor